Highly-resistant E. coli as a Common Cause of Paediatric Diarrhoea in India (Journal of Health, Population and Nutrition, 2013)
Abstract not available DOI: http://dx.doi.org/10.3329/jhpn.v31i3.16835 J HEALTH POPUL NUTR 2013 Sep; 31(3): 409-412